Modelamiento de la calidad del aire en la ciudad de Cuenca-Ecuador (2015)
The air quality monitoring performed in the city of Cuenca, pollution problems became evident, therefore a more detailed study related to the dispersion and transport of contaminants was conducted. In this context two dispersion models such as: DISPER5.2 and WRF/Chem, were applied to analyze the quality of modeling, degree of approximation and limitations. The Geographic Information System ArcGIS allowed visualization the maps generated from the models. The DISPER5.2 model showed a low quality modeling, due to limited resolution simulation, modeling is punctual and no relationship between all input data. The second model (WRF/Chem), established a relationship between geographic and meteorological data of the study area with chemistry and pollutant dispersion, reporting results with high resolution in both: local and global areas. In addition, the lack of information regarding emissions of  ollutants to feed the model and continuous monitoring devices was evident.